Jurisprudential and legal support in Cases of Unusual and Unauthorized Sexual Behaviors in Domestic Sexual Violence in Iran: A Review Article - Fatemeh Ghodrati (Mashhad University of Medical Sciences, 2022)
Background & aim: Inadequate laws to prevent sexual violence against women and to protect victims as well as the factors such as patriarchal culture, and misconceptions of some religious and Islamic teachings can lead to temper divorce and betrayal. This study was performed to review the jurisprudential and legal protections for domestic sexual violence in Iran.Methods: In this review, the published evidence on the supportive aspects of domestic sexual violence between 1990 and 2021 was searched in the English database of Scopus, PubMed, Science Direct, and EBSCO as well as Persian databases of Magiran, SID, and IranMedex. To collect data, searching was done using the key words of Violence, Domestic, Family Violence, Sex Offenses, Partner Abuse, Sexual Violence, Civil Law, legislation, jurisprudence and religion of Islam alone or in combination in English and their Persian equivalents.Results: Among 69 studies related to the legal and religious aspects of sexual violence, 35 studies were reviewed. In Iranian law, there is legal material only in a number of cases of sexual violence in the section on punishments and the Islamic Penal Code. There is also disagreement among Shiite scholars about some unusual sexual behaviors. Ongoing counseling is emphasized due to the importance of different dimensions such as unconventional sexual request, and sexual violence with reluctance of wife.Conclusion: Some cases of sexual violence are not properly restricted. Therefore, more attention to these cases by jurists and legislators can reduce the occurrence of many forms of sexual violence against women.